Receiving the mental health user: perceptions of professionals committed to the Family Health Strategy - Mônica Barreto; Aline Aparecida Foppa; Maria Fernanda Cabral; Jadete Rodrigues Gonçalves; Carmen Leontina Ojeda Ocampo More (Universidade de Brasília, 2010)
.